PENGARUH PARTISIPASI ANGGARAN TERHADAP KESENJANGAN ANGGARAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI (Studi Pada Rumah Sakit Umum Daerah (RSUD) Dan RSI Sultan Agung Di Kota Semarang) - Indriani, Listya; Yusuf, Muhammad (PRESTASI, 2014)
ABSTRACTÂ Organizational culture is a factor that determines tJhe characteristics of an organization. Study of organizational culture has a significant value in researching an organization. Organizational culture study shows how a culture develops in an organization, internalized in the behavior of the members of the organization, and have a relationship with the over all performance of the said organization. Culture of the organization with other organizations are relatively different, depending on the characteristics of the organization it self. In this case, the private hospital organizations have cultural differences with the government hospital organization. The purpose of this study to determine the effect of budgetary participation on budgetary slack, the influence of organizational culture on work-oriented and people-oriented budget participation on the relationship with the budgetary slack. In this study for samples using convenience sampling technique. Samples were selected in this study is the manager or manager-level Regional General Hospital (RSUD) and RSI Sultan Agung. Data analysis method used is simple linear regression analysis and moderated regression analysis (MRA). The results showed that budgetary participation has a positive effect on the budgetary slack, the organizational culture oriented jobs weakens the negative effect on the relationship between budgetary participation budgetary slack, and the culture of a people-oriented organization that positively strengthen the relationship between budgetary participation of the budgetary slack. Â Keywords: Budget Participation, Organizational Culture, Budgetary Slack